Short-term Correction of Arginase Deficiency in a Neonatal Murine Model With a Helper-dependent Adenoviral Vector - Gau, Chia-Ling (Nature Publishing Group, 2009)
Neonatal gene therapy has the potential to ameliorate abnormalities before disease onset. Our gene knockout of arginase I (AI) deficiency is characterized by increasing hyperammonemia, neurological deterioration, and early death. We constructed a helper-dependent adenoviral vector (HDV) carrying AI and examined for correction of this defect. Neonates were administered 5 × 10(9) viral particles/g and analyzed for survival, arginase activity, and ammonia and amino acids levels. The life expectancy of arg(−/−) mice increased to 27 days while controls died at 14 days with hyperammonemia and in extremis. Death correlated with a decrease in viral DNA/RNA per cell as liver mass increased. Arginase assays demonstrated that vector-injected hepatocytes had ~20% activity of heterozygotes at 2 weeks of age. Hepatic arginine and ornithine in treated mice were similar to those of saline-injected heterozygotes at 2 weeks, whereas ammonia was normal. By 26 days, arginase activity in the treated arg(−/−) livers declined to <10%, and arginine and ornithine increased. Ammonia levels began increasing by day 25, suggesting the cause of death to be similar to that of uninjected arg(−/−) mice, albeit at a later time. These studies demonstrate that the AI deficient newborn mouse can be temporarily corrected and rescued using a HDV.